Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids (CLIPPERS Syndrome): A Case Report and Literature Review - Nripesh Man Shrestha; Niranjan Acharya; Rabindra Desar (Case Reports in Neurological Medicine, 2023)
CLIPPERS is a rare, chronic inflammatory neurological syndrome affecting multiple regions of the brain including the brainstem, cerebellum, and spinal cord. More than 100 cases have been documented globally since its initial description in 2010. This article reports the first case of the CLIPPERS syndrome in Nepal. Clinical and radiological evidences of the patient lead to the diagnosis of this disease. Brain MRI reveals punctate and curvilinear gadolinium enhancement in the pons and cerebellum, which is diagnostic for the disease. Steroid therapy has been reported to be effective in treating CLIPPERS syndrome. Although its pathophysiology indicates an immune-mediated process, the etiology is yet unknown. The treatment and prognosis of this illness depend on an early and accurate diagnosis.